Terapia ocupacional e tecnologia assistiva: funcionalidade para pessoas com artrite reumatoide - Paula, Pryscilla Mychelle da Silva (2017)
Rheumatoid arthritis is a chronic, systemic autoimmune disease characterized by inflammation of the synovial membrane of peripheral joints. People with rheumatoid arthritis frequently require assistive technology resources that are conceptualized in the search for solutions in the field of integral accessibility, recognized as a fundamental element in rehabilitation and social inclusion, promoting the independence of people with disabilities. Objectives: To describe the sociodemographic and clinical characteristics of people with rheumatoid arthritis, to quantify those who have difficulties to perform daily life activities and to define the ideal assistive technology for each type of limitation. Patients and Methods: A prospective, quantitative, descriptive, clinical study was carried out with 198 people attending the outpatient clinic of a general hospital. A questionnaire on general and clinical data and a validated survey assessing limitations in daily life and instrumental activities, the Health Assessment Questionnaire (HAQ), were used for data collection. Results: The mean age was 57.9 (SD ± 11.2) years, there was a predominance of women between 51 and 67.9 years old (n = 107; 54%), most had not completed elementary school (n = 127; 64.1%) and were homemakers (n = 80; 40.4%). The survey identified that 98 (49.5%) people found it very difficult or impossible to climb stairs, 75 (37.9%) to raise their arms or take a high-up object, 65 (32.8%) to bend over to pick clothes up from the floor, 94 (47.5%) to remain standing on a bus, 73 (39.9%) to shop in their local shops, 80 (40.4%) to get on/off buses and 70 (35.4%) to sweep or mop the floor. Conclusions:There is a need to expand the indications by the professionals, to follow the adhesion of use by the patient, identifying their potentialities and difficulties. It is necessary to guide the family member who will advise the individual in their activities, clarifying about these resources and their importance for their social inclusion, and especially about how assistive technologies can prevent deformities in people with rheumatoid arthritis.